The Stress Experienced and Coping Strategies Adopted by the Mothers of Children Suffering from Leukemia - Ms. Purkait Gita; Sonali Ganguly; Toma Dey (Indian Journal of Psychiatric Nursing)
The main purpose of the study was to identify the stress experienced by the mothers of children suffering from leukemia and the related coping strategies. Methods: A descriptive co-relational design was chosen for the present study to find relationship with the level of stress experienced and coping strategies adopted by the mothers of the children suffering from leukemia, relationship between stress and selected variables and relationship of coping and selected variables. The sample subjects of the study were 70 mothers of the children suffering from leukemia at the outpatient and inpatient departments of the institution(N.C.R.I.), Kolkata. Tools were: Tool 1) A Structured scale to measure the stress of the mothers (4 points rating scale) and 2) A Structured questionnaire to assess Coping Strategies adopted by the mothers (a check list). Results: Most of the mothers i.e. 28 out of 70 (40 %) of the mothers of children suffering from leukemia were in the age group 20-30 years, majority mothers 43 out of 70 (61.43 %) were from lower socio-economic group. From the major findings of the study it is shown that majority of the mothers of children suffering from leukemia had been experiencing moderate level of stress and coping strategies adopted by them in most of the samples also were moderately successful. There is negative correlation between the experienced stress and adopted coping strategies; i.e. when stress experience is increasing, coping is decreasing and significantly as well. There was no association found between stress and selected variables and coping strategy also has no association with selected variables.